Written in racialized bodies. Language, memory and genealogies (post) colonial femicide in Latin America - Bidaseca, Karina Andrea (2013)
Since 1993, the term femicide has referred to a continuous wave of crimes committed to women due to gender or race, a structural feature of our societies. This paper inscribes the question on the limits of the representation of the unutterable in our local post-colonial genealogies. How could we write a feminist narrative symbolically able to inscribe the losses within it, and question the world outside? This shows that all efforts in favor of Politics of Memory must be founded in the recovery of silenced First People languages, and in the cross-disciplinary junction of Art and Social Sciences.